A real-world study for timely assessing the diabetic macular edema refractory to intravitreal anti-VEGF treatment - Hsieh, Tsung-Cheng; Deng, Guang-Hong; Chang, Yung-Ching; Chang, Fang-Ling; He, Ming-Shan (Frontiers in Endocrinology, 2023)
Background: Early Identifying and characterizing patients with diabetic macular edema (DME) is essential for individualized treatment and outcome optimization. This study aimed to timely investigate optical coherence tomography (OCT) biomarkers of DME refractory to intravitreal anti-vascular endothelial growth factor (VEGF) therapy. Methods: We retrospective reviewed 72 eyes from 44 treatment-naïve patients who were treated with intravitreal anti-VEGF for DME. OCT scans prior to anti-VEGF were evaluated for serous retinal detachment (SRD), size of outer nuclear layer cystoid changes, diffuse retinal thickening, integrity of the inner segment-outer segment (IS-OS) junction, quantity and location of hyperreflective foci, vitreomacular interface abnormalities, and epiretinal membrane (ERM). The Baseline best-corrected visual acuity (BCVA) and central macular thickness was recorded at baseline and 4 months after treatment with anti-VEGF. The main outcome measure was the correlation between spectral-domain OCT measurements and BCVA response at baseline and after anti-VEGF treatment (mean change from baseline; ≥ 10 Early Treatment Diabetic Retinopathy Study letters in BCVA). Results: Partially continuous IS-OS layers (partially vs. completely continuous: β, -0.138; Wald chi-square, 16.392; P<0.001) was predictor of better response to anti-VEGF treatment. In contrast, ERM (present vs. absent ERM: β, 0.215; Wald chi-square, 5.921; P=0.015) and vitreomacular traction (vitreomacular traction vs. posterior vitreous detachment: β=0.259; Wald chi-square=5.938; P=0.015) were the predictors of poor response. The improvement of BCVA trended toward the OCT predictive value of central macular thickness reduction; however, this was not significant. Conclusion: Partially continuous IS-OS layers is predictive of better response to anti-VEGF therapy in DME. Meanwhile, ERM is a significant predictor of poor response.